Lignocellulose-Adapted Endo-Cellulase Producing Streptomyces Strains for Bioconversion of Cellulose-Based Materials - Ventorino, Valeria; Ionata, Elena; Birolo, Leila; Montella, Salvatore; Marcolongo, Loredana; de Chiaro, Addolorata; Espresso, Francesco; Faraco, Vincenza; Pepe, Olimpia (Frontiers in Microbiology, 2016)
Twenty-four Actinobacteria strains, isolated from Arundo donax, Eucalyptus camaldulensis and Populus nigra biomasses during natural biodegradation and with potential enzymatic activities specific for the degradation of lignocellulosic materials, were identified by a polyphasic approach. All strains belonged to Streptomyces (S.) genus and in particular, the most representative species was S. argenteolus including the 50% of strains; while 8 strains were identified as members of species S. flavogriseus (synonym S. flavovirens) and S. fimicarius (synonyms S. acrimycini, S. baarnensis, S. caviscabies and S. flavofuscus), and the other 4 strains belonged to the species S. drozdowiczii, S. rubrogriseus, S. albolongus and S. ambofaciens. Moreover, all Streptomyces strains, tested for endo and exo-cellulase, cellobiase, xylanase, pectinase, ligninase, peroxidase and laccase activities using qualitative and semi-quantitative methods on solid growth medium, exhibited multi-enzymatic activities (from three to six). The twenty-four strains were further screened for endo-cellulase activity in liquid growth medium and the four best endo-cellulase producers (S. argenteolus AE58P, S. argenteolus AE710A, S. argenteolus AE82P and S. argenteolus AP51A) were subjected to partial characterization and their enzymatic crude extracts adopted to perform saccharification experiments of Arundo donax pretreated biomass. The different degrees of cellulose and xylan hydrolysis was evaluated by determining the kinetics of glucose and xylose release during 72 h incubation at 50°C of the pretreated biomass in the presence of cellulose degrading enzymes (cellulase and β-glucosidase) and xylan related activities (xylanase and β-xylosidase). Cellulose and xylan conversion, when conducted using commercial (hemi)cellulolytic, gave glucose and xylose yields of 30.17% and 68.9%, respectively. The replacement of the cellulolytic preparation from Genencor (Accellerase 1500), with the endo-cellulase from S. argenteolus AE58P allowed to reach almost the 76% of the glucose yield obtained in the presence of the commercial counterpart. Due to the promising results obtained by using the enzymatic crude extracts from S. argenteolus AE58P in the pretreated A. donax saccharification experiments, the proteins putatively responsible for endo-cellulase activity in this strain were identified by proteomics. Overall results highlighted the biotechnological potential of S. argenteolus AE58P being an interesting candidate biocatalysts-producing bacterium for the lignocellulose conversion and biochemicals and bioenergy production.